FACTORS OF USING CASHLESS TRANSACTIONS IN RETAIL BUSINESS USING GROUNDED THEORY - Givianty, Vasya Theodora; Kurinawan, Haby; Julian, Ahmad; Heikal, Jerry (AKSELERASI: Jurnal Ilmiah Nasional, 2024)
Today's technological developments have been able to influence almost all business sectors so that business actors inevitably have to be able to keep up with these technological developments if they want to survive in the business world. One sector that is very dynamic following these developments is the banking sector. Developments in this sector have a domino effect on other sectors because banking acts like a bridge between business actors. The product results from this sector which can be said to be one of the factors changing consumer behavior is e-banking which encourages the creation of cashless (non-cash) transactions. Apart from that, the increasing type and number of smartphones has contributed to the growth of transactions via e-banking. This research uses qualitative techniques with a grounded theory approach. The author conducted direct interviews with several business actors in the retail sector to determine the influence of e-banking in increasing transactions. Based on the research results, it was found that the coding scheme consisted of 17 codes which formed 7 categories and gave rise to 3 themes with a total frequencies of 25. The highest frequency in coding was 12 on the theme of ease of transactions and 10 on the theme of security so that the factors that influence the use of cashless e-banking are making it easier. buying and selling transactions of business actors in the retail sector and reducing the risk of fraud during transactions compared to increasing transaction volume.